Directly anchoring 2D NiCo metal–organic frameworks on few-layer black phosphorus for advanced lithium-ion batteries. Issue 2 (17th December 2018) - Jin, Jun; Zheng, Yun; Huang, Shao-zhuan; Sun, Ping-ping; Srikanth, Narasimalu; Kong, Ling Bing; Yan, Qingyu; Zhou, Kun
Abstract : A 2D few-layer black phosphorus/NiCo MOF (BP/NiCo MOF) hybrid is rationally designed and directly utilized as a lithium-ion battery anode. Abstract : Tremendous research efforts have been made to develop advanced lithium-ion battery (LIB) anode materials with high capacity, long cycle life and excellent rate capability. Metal–organic frameworks (MOFs) are regarded as appealing candidates to address the issues such as huge volume change, pulverization and sluggish ion transport kinetics. In this work, a 2D few-layer black phosphorus/NiCo MOF (BP/NiCo MOF) hybrid is rationally designed and prepared through a facile route in a solution of Ni 2+, Co 2+ and benzenedicarboxylic acid (BDC) at room temperature. The carboxylate groups in BDC 2− can not only chelate with metal ions but also bond with BP, resulting in a stable 2D hybrid structure. The BP/NiCo MOF electrode can provide abundant redox-active sites and ensure high Li + storage capability. The 2D nanostructure and porous structure of BP/NiCo MOF can not only provide favorable pathways for charge transport but also buffer the volume change upon cycling, leading to the enhanced electrochemical performance with good cycling stability and excellent rate capability. The rationally designed 2D BP/NiCo MOF demonstrates high reversible capacity (853 mA h g −1 at 0.5 A g −1 ), long cycle life and excellent high rate capability (398 mA h g −1 at 5 A g −1 after 1000 cycles).